The Promotion and Communication of Occupational Health and Safety at PT Pertamina International (KPI) Refinery Unit Balongan - Indramayu - Windiari, Ira Puspita; Madoeretno, Amiroel Pribadi; Jannah, Roihatul (Gema Wiralodra, 2024)
Pertamina Internasional (KPI) Refinery Unit VI Balongan is one of the refineries of PT. Pertamina (Persero) processes oil and natural gas into BBM (Fuel Oil), non-fuel and Petrochemical products. Potency the dangers that exist at PT. Pertamina International (KPI) RU VI Balongan Refinery, starting from mild potential dangers to potentially fatal dangers. Taking precautions requires a form of preventing work accidents. This research aims to discover programs, procedures and implementation Promotion and Communication of Occupational Health and Safety (OHS) carried out by PT. Pertamina Internasional (KPI) Refinery unit VI Balongan. The research method used was descriptive qualitative. Data collection methods use field observations, interviews, and literature studies. The population in this study was the HSSE Department. Descriptive data management method. In results of this observation, there is an Occupational Health and Safety (OHS) Promotion and Communication program implemented by PT. Pertamina International Refinery (KPI) Refinery unit VI Balongan includes Grand Safety Talk, Safety Walk and Talk, Toolbox Meeting, OHS Signs, and Tank Module Extinguishing Training at the Fire Ground. Promotion procedures OHS at PT. Pertamina Internasional (KPI) Refinery unit VI Balongan refers to company procedures, namely TKO No. B07-022/KPI49530/2022-S9 1st Revision concerning Implementation of Safety Communication and TKI No. C07-004/KPI49520/2022-S9 regarding the Implementation of Tank Module Outage Simulations at the Fire Ground. Implementation of Occupational Health and Safety Promotion and Communication programs (OHS) for OHS communication related to the toolbox meeting is not by the procedures and the implementation of OHS training is by the procedures.